Alternative strategies for mosquito-borne arbovirus control - Achee, Nicole L. (2019)
Background: Mosquito-borne viruses—such as Zika, chikungunya, dengue fever, and yellow fever, among others—are of global importance. Although vaccine development for prevention of mosquito-borne arbovirus infections has been a focus, mitigation strategies continue to rely on vector control. However, vector control has failed to prevent recent epidemics and arrest expanding geographic distribution of key arboviruses, such as dengue. As a consequence, there has been increasing necessity to further optimize current strategies within integrated approaches and advance development of alternative, innovative strategies for the control of mosquito-borne arboviruses. Methods and findings: This review, intended as a general overview, is one of a series being generated by the Worldwide Insecticide resistance Network (WIN). The alternative strategies discussed reflect those that are currently under evaluation for public health value by the World Health Organization (WHO) and represent strategies of focus by globally recognized public health stakeholders as potential insecticide resistance (IR)-mitigating strategies. Conditions where these alternative strategies could offer greatest public health value in consideration of mitigating IR will be dependent on the anticipated mechanism of action. Arguably, the most pressing need for endorsement of the strategies described here will be the epidemiological evidence of a public health impact. Conclusions: As the burden of mosquito-borne arboviruses, predominately those transmitted by Aedes aegypti and A. albopictus, continues to grow at a global scale, new vector-control tools and integrated strategies will be required to meet public health demands. Decisions regarding implementation of alternative strategies will depend on key ecoepidemiological parameters that each is intended to optimally impact toward driving down arbovirus transmission.